Effects of cadmium exposure during the breeding period on development and reproductive functions in rare minnow (Gobiocypris rarus) - Su, Liangxia; Li, Huanhuan; Qiu, Ning; Wu, Yinrui; Hu, Bing; Wang, Rui; Liu, Jun; Wang, Jianwei (Frontiers in Physiology, 2023)
Cadmium (Cd) is a common reproductive toxin in aquatic systems. Parental Cd exposure of fish species at high concentrations can severely affect the reproductive function of fish. However, the influence and mechanisms underlying parental Cd exposure at low concentrations on the reproductive function in parental fish remains unclear. To investigate the impacts of parental Cd exposure on reproductive capability, eighty-one male and eighty-one female rare minnows (Gobiocypris rarus) were exposed to Cd at 0 (control group), 5 and 10 μg/L for 28 days, and then transferred into clean water to pair spawn. The results showed that parental Cd exposure at 5 or 10 μg/L for 28 d in rare minnows could reduce the success rates of pair spawning in parent rare minnows, lessen no-spawning activities, and prolong the time for first spawning. Furthermore, the mean egg production of the parental Cd exposure group increased. The fertility rate of the parental 10 μg/L Cd exposure group was significantly higher than that of the parental 10 μg/L Cd exposure group. Anatomical and histological data further revealed that the intensity of atretic vitellogenic follicles significantly increased and spermatozoa vacuolated after parental Cd exposure (P < 0.05), but slightly increased the CF, and relatively stable GSI values were also observed in the parental Cd exposure groups. These observed results indicated that parental Cd exposure at 5 or 10 μg/L severely affected the reproductive activity of paired rare minnow by accumulating Cd in the gonads, and the effect diminished over time. The reproductive risk of low-dose Cd exposure to fish species remains a cause for concern.